(untitled) (Hoboken, N.J., 2013)
This book describes methodology and applications for endocrine disrupter toxicity testing, an issue of considerable urgency, because of international regulatory authorities currently considering such testing schemes. The coverage examines major animal groups for sensitivity to endocrine disrupting chemicals (EDCs), identifying endpoints and procedures for testing guidelines. Three EDC screening methods (two using fish and one using amphibians) are examined in detail for their efficacy and applicability. Edited by, and with contributions from, a leading participant in regulatory efforts, the book outlines methods that combine sensitivity, efficiency, statistical power, acceptable cost, and minimum ethical concern
Keywords: Endocrine-disrupting chemicals,Hóa chất gây ảnh hưởng nội tiết; Toxicity testing.,Thử nghiệm độc tính